Cone beam computed tomography-guided thin/ultrathin bronchoscopy for diagnosis of peripheral lung nodules: a prospective pilot study - Casal, Roberto F.; Sarkiss, Mona; Jones, Aaron K.; Stewart, John; Tam, Alda; Grosu, Horiana B.; Ost, David E.; Jimenez, Carlos A.; Eapen, George A. (Journal of Thoracic Disease, 2018)
Background: Despite advances in bronchoscopy, its diagnostic yield for peripheral lung lesions continues to be suboptimal. Cone beam computed tomography (CBCT) could be utilized to corroborate the accuracy of our bronchoscopic navigation and hopefully increase its diagnostic yield. However, data on radiation exposure and feasibility of CBCT-guided bronchoscopy is scarce. Methods: Prospective pilot study of bronchoscopy for peripheral lung nodules under general anesthesia with thin/ultrathin bronchoscope, radial-probe endobronchial ultrasound (RP-EBUS), and CBCT. Main objective was to estimate radiation dose and secondary objective was the additional value of CBCT in terms of navigational and diagnostic yield. Results: A total of 20 patients were enrolled. Median lesion size was 2.1 (range, 1.1–3) cm and distance from pleura was 2.1 (range, 0–2.8) cm. “Bronchus sign” was present in 12 (60%) of the lesions. Totally, 12 lesions (60%) were invisible on fluoroscopy. CBCT identified atelectasis obscuring the target in 4 cases (20%). Eleven patients (55%) underwent 1 CBCT scan and 9 patients (45%) 2. The mean estimated effective dose (E) to patients resulting from CBCT ranged between 8.6 and 23 mSv, depending on utilized conversion factors. Both pre-CBCT navigation and diagnostic yield were 50%. Additional post-CBCT maneuvers increased navigation yield to 75% (P=0.02) and diagnostic yield to 70% (P=0.04). One patient developed a pneumothorax. Conclusions: CBCT-guided bronchoscopy is associated with an acceptable radiation dose. CBCT may potentially increase both navigation and diagnostic yield of thin/ultrathin bronchoscopy for peripheral lung nodules. The above findings as well as the incidental but relevant finding of intra-procedural atelectasis need to be confirmed in larger prospective studies. Trial registration: This study is registered in ClinicalTrials.gov as number NCT02978170.